KidBus.Tracker: The Development of a Schoolchildren Identification and Transportation Tracking System (International Journal of Innovative Computing, 2017)
There are approximately five million Malaysian children commuting to school every day. Approximately 40 percent of these schoolchildren rely on public and private school transportation. There have been cases that of children kidnapping reported in the news in recent years. The news on these cases is amplified further in social media and has caused concerns to parents. Nonetheless, some parents do not have an option in sending their children to school. Busy schedule and hectic working lives are key factors in the parent’s decision to use public or private school transportation services. The use of these services exposes schoolchildren to risks such as kidnapping and accidents. Parents, on the other hand, could not monitor the safety of their children in commuting to and from school. This paper presents a system called KidBus.Tracker that monitors schoolchildren's commute to school. The system was developed using global positioning satellite (GPS) tracking as a way to track the school vehicle, while passive radio frequency identification (RFID) technology was used to record the children’s presence on the vehicle. The data log captured from the hardware would then be extracted and processed by the server. Parents would be able to monitor the school vehicle’s movement while their children are on board the school transport through the KidBus.Tracker website. The findings of the user acceptance test indicate that KidBus.Tracker can give parents ease of mind when their children are commuting to and from school using school transportation services.